Links of consciousness, perception, and memory by means of delta oscillations of brain - Düzgün, Aysel; BAŞAR, EROL (Frontiers Media Sa, Po Box 110, EPFL Innovation Park, Building I, Lausanne, 1015, Switzerland, 2016)
The aim of this report is threefold: (1) First, we accomplish a survey integrating the description of consciousness, perception, and memory according to the views of descriptions of Hermann Helmholtz, Sigmund Freud, Henri Bergson, and Gustav Jung. (2) In the second step, we present experimental results for defining the machineries of sensation and perception:(a) electrical responses of isolated ganglion of Helix pomatia were measured upon odor stimuli that elicited varied degrees of responses. Such a model may give an idea of the control of sensation in the preconscious state of a living tissue.(b) We also describe experiments at the human hearing threshold level.(c) Further, the omission of working memory will be shown with the attenuation of delta response in Alzheimer's subjects in P300 measurements.(d) Finally, the measurement of auditory evoked potentials during slow-wave sleep in the cat brain explains the auditory responses that are not heard at this level of consciousness. (3) In the third step, we aim to provide a synopsis related to integration of perception, memory, and consciousness. By using concepts of important scientists as S. Freud on consciousness, we also tentatively discuss the boundaries of the transition of unconsciousness states to conscious states.
Keywords: top-down; P300; working memory; perception; consciousness; unconsciousness; brain oscillations